Use of Blended Learning in Teaching Islamic History: The Case of the 8th Grade of Sukma Bangsa School in Aceh - Lesmana, Adhi; Basiran, Basiran (Yayasan Sukma Bangsa, 2018)
The article is intended to introduce blended learning methods at Sukma Bangsa School, Aceh. The purpose of this study is to demonstrate the effectiveness of blended learning method specifically in the study of Islamic history, which is one of the main topics in religion education lessons in the 8th grade at the three different locations of Sukma Bangsa School. The study uses quantitative methods and was carried out during the first semester of the school year 2015 -2016 in the three locations of Sukma Bangsa School. Research data was obtained through the pre-test and the post-test that were conducted at the beginning of the research and the end of the research. The total number of students in this study was 142 students: 57 students from Bireuen, 34 students from Pidie, and 51 students from Lhokseumawe. The results of the study at the three different locations of Sukma Bangsa School show that although there was an increase in the average value and standard deviation, the statistics do not show a significant difference between the achievement of students in the blended learning method and in the face-to-face method. Therefore, an understanding of context by the teachers in the use of blended learning is needed to improve students’ achievement results.[Artikel ini dimaksudkan untuk lebih mengenalkan metode pengajaraan blended learning di Sekolah Sukma Bangsa, Aceh. Tujuan dari penelitian ini adalah untuk menunjukkan adakah keefektifan metode blended learning secara khusus di materi Sejarah Islam yang merupakan salah satu topik utama dalam pelajaran pendidikan agama di kelas 8 di tiga lokasi Sekolah Sukma Bangsa. Studi ini menggunakan metode kuantitatif dan dilakukan di Sekolah Sukma Bangsa Bireuen, Pidie, dan Lhokseumawe pada semester ganjil tahun pelajaran 2015-2016. Data dalam penelitian ini diperoleh melalui hasil pre-test dan post-test yang dilakukan di awal sebelum penelitian dan menjelang akhir penelitian. Total siswa yang mengikuti penelitian ini sebanyak 142 siswa dengan rincian 57 siswa di Sukma Bangsa Bireuen, 34 siswa di Sukma Bangsa Pidie, dan 51 siswa di Sukma Bangsa Lhokseumawe. Hasil studi di tiga lokasi Sekolah Sukma Bangsa menunjukkan bahwa meskipun ada peningkatan nilai rata-rata dan standard deviasi namun secara statistik tidak menunjukkan perbedaan yang significant antara hasil pencapaian siswa di metode blended learning dan di metode tatap muka. Oleh karena itu pemahaman guru secara kontekstual dalam penggunaan blended learning sangat dibutuhkan untuk meningkatkan hasil pencapaian siswa.]